Faktor-faktor kejayaan perusahaan kecil dan sederhana (PKS) muslim: amalan agama islam sebagai penyederhana - Nadratun Nafisah, Abdul Wahab (2018)
This study is about the Islamic SMEs success factors in Malaysia. The failure of Muslim SMEs is alarming. To date, empirical references to Muslim SMEs are limited, especially focusing on religious practice factors. Therefore, this study is conducted to test the relationship of innovative, risk, proactive, motivational and networking to SMEs success and religious practices as moderator. Specifically, the first goal is to identify the relationship between innovation, risk, proactivity and motivation towards the success of Muslim SMEs. The second objective is to identify the relationship between networking and Muslim SMEs success. Next is the third goal to measure the influence of religious practices as a moderator to the relationship of independent variables, innovations, risks, proactives, motivations and networks (independent variables) to help the success of Muslim SMEs (dependent variables). This study uses the Resource-Based View (RBV) theory, in describing the research theoretical framework. The method used is quantitative. Respondents involved were 122 firms selected through simple random sampling from 2286 PUNB entrepreneurs in Malaysia. The findings show that three innovative, proactive and network variables have the potential to influence the success of the firm. Although risk and motivation are not supported. This study also found that the moderation factor in religious practice affects the relationship between the network and the success of Muslim SMEs. The findings show that religious practices have been highlighted as a contribution to entrepreneurship knowledge, especially entrepreneurship success among Muslim SMEs in Malaysia. In addition, this study found that the measurement of firm practices variable has surpassed the level of validity and reliability that can be used for future research.